Pembinaan Pengurus Pesantren Tentang Kepemimpinan Dalam Islam Menurut Al-Qur’an Dan Hadist di Pondok Pesantren Mukhtar Syafa’at Blokagung Tegalsari Banyuwangi - Mahmudah Mahmudah; Ahmad Munib Syafa'at; Muhammad Imam Khaudli; Muhammad Riza Aziziy (IAI Darussalam, 2022)
Pesantren as an educational institution as well as a religious institution is quite interesting to observe from various sides, including leadership. The purpose of this service is to develop boarding school administrators about leadership in Islam according to the Qur'an and Hadith at the Mukhtar Syafa'at Islamic Boarding School Blokagung Tegalsari Banyuwangi to strengthen the potential of students in leading. The importance of knowledge and understanding of students regarding leadership becomes a guide for students when interacting with the community.